Pelestarian Identitas Masyarakat Multietnis Kampung Melayu - Febriyanti, Ika; Zulfiningrum, Rahmawati (Medium: Jurnal Ilmiah Fakultas Ilmu Komunikasi, 2025)
Kampung Melayu Semarang is a historic area that reflects the ethnic and cultural diversity of the community in Semarang's Old Town. However, amid the city's modernization and tourism growth, there has been a decline in youth participation and a weakening of the community's understanding of the meaning of local traditions. This study aims to analyze how cultural identity and efforts to preserve the traditional values of a multi-ethnic community are manifested through the Kirab Budaya (Cultural Parade) activity. The research uses a descriptive qualitative approach with an interpretive paradigm, using cultural identity theory to understand the social construction of identity and the concept of cultural preservation to examine the sustainability of local values. Data collection techniques were carried out through participatory observation, in-depth interviews, and documentation, which were then analyzed through the stages of data reduction, data presentation, and conclusion drawing. The results of the study show that cultural parades not only serve as a form of cultural expression, but also as a mechanism to strengthen shared identity among multi-ethnic communities. This identity is clearly seen through various traditional symbols in cultural parades, such as traditional clothing, Zapin dance, and rebana music, as well as the involvement of various ethnic groups. This cultural parade also serves as a means of preserving intangible cultural heritage, involving the active participation of local residents and the younger generation, while strengthening social solidarity and reviving the Malay-Islamic values that form the basis of community identity in Semarang. The Kampung Melayu Cultural Parade plays an important role in maintaining the continuity of multi-ethnic identity and preserving local cultural values amid massive social changes in urban communities. Keywords: preservation, multiethnicity, tourism, traditional symbols, cultural heritage